The role of formalization and organizational trust as antecedents of ambidexterity: An investigation on the organic agro-food industry - Odette Chams-Anturi; Maria D. Moreno-Luzon; Pietro Romano (BRQ Business Research Quarterly, 2022)
This article investigates the influence of specific key organizational factors (i.e., enabling formalization, coercive formalization, and trust) as antecedents of ambidexterity. Moreover, we propose a new way of operationalizing ambidexterity, under a holistic vision, including the synergies between exploration and exploitation. The study has been developed in the Spanish organic agro-food industry; a total of 239 usable responses were received from two respondents from each company - the general manager and the quality manager. The findings show that enabling formalization and organizational trust are positively related to ambidexterity, but contrary to our predictions, we found no evidence to show that coercive formalization is related to ambidexterity. In turn, we found different results for trust as a moderating factor on the types of formalization and ambidexterity.
Keywords: M10; M12; 650; Ambidexterity; formalization; organic agro-food industry; organizational trust